World Christian encyclopedia a comparative survey of churches and religions in the modern world - Barrett, David B.; Kurian, George Thomas 1931-; Johnson, Todd M. 1958- (Oxford [u.a.] Oxford University Press, 2001)
Here is the completely updated and greatly expanded new edition of a classic reference source--the comprehensive overview of the world's largest religion in all its many versions and in both its religious and secular contexts. Now in two volumes, the Encyclopedia presents and analyzes an unmatched wealth of information about the extent, status, and characteristics of twentieth-century Christianity worldwide. It takes full account of Christianity's ecclesiastical branches, subdivisions, and denominations, and treats Christianity in relation to other faiths and the secular realm. It offers an unparalleled comparative study of churches and religions throughout the modern world. This new edition features a vast range of new and previously unpublished data on the current global situation of Christianity, on religion in general, and on the political, demographic, economic, and social characteristics of the world's cultures and peoples in 238 countries. Each volume is filled with essential information, from historical surveys of denominations to country-by-country profiles of churches and believers. The text sets the cxurrent status of Christianity into a rich historical context, and assesses current trends and future directions. Many tables, charts, diagrams, photographs, a directory of names and organizations, a glossary, index, and other features ensure accessbility for specialists and non-specialists alike. The Encyclopedia will be of great value to academics of many disciplines, clergy, administrators, and those who work in Christian and other religious organizations around the world, as well as to anyone interested in current affairs. - Complete, authoritative, and up-to-date survey of world Christianity in two volumes. Five major subject areas, -countries, religions, cities, languages, and peoples. Compiled by over 500 experts representing the Ecumenical, Protestant, Catholic, Orthodox, Evangelical, Charismatic, academic, other world-religionist, non-Christian, and secular worlds. Country-by-country look at the religious and secular makeup of 251 nations. Includes political, economic, demographic, linguistic, ethnic, and cultural data in narrative text as well as in tabular and graphic form. Extensively illustrated with numerous photographs, graphics, sidebars, maps, and diagrams. Helpful apparatus, bibliography, glossary, directory of names and addresses, and several quick-reference indexes
Keywords: Christianity; Christian Sects; Ecclesiastical geography; Christianity -- Statistics; Wörterbuch